Aorto caval fistula—the "bursting heart syndrome". Issue 3 (1st May 2000) - Leigh-Smith, S; Smith, R C
Abstract : Aorto caval fistula is one of the less well recognised complications of abdominal aortic aneurysm seen in accident and emergency departments. It presents in a number of different ways the commonest of which is high output congestive cardiac failure with warm peripheries. Initial diagnosis is based on the index of suspicion of the clinician. However, early diagnosis by the emergency physician and early surgery can markedly improve the patients prognosis.